The urgency of foreign direct investment in micro, small, and medium enterprises financing framework: the case of Indonesia - Kaukab, M. Elfan (Business: Theory and Practice, 2023)
This research aims to check whether the rate of production growth in the MSME sectors open to foreign direct investment (FDI) was lower than in the closed MSME sectors before the policy in 2016 and whether the growth rate of the open MSME sectors’ production lower than the closed MSME sectors after the policy in 2016. The study covers a period of 9 years from 2011 to 2020 based on the data from Indonesian Statistics Bureau. Data used was industrial sectors’ performance, classified into closed and open for FDI sectors. The classification is defined based on Presidential Regulation No. 44 of 2016. In total there are 13 closed and 10 open sectors. We analyse the data using t-test analysis between closed and open FDI industrial sectors. The results of the study found that the performance of open MSMEs was significantly lower than the performance of closed MSMEs, both before and after the liberalization. Therefore, the government must relax the requirements given to investors to invest in open MSMEs.